2019
DOI: 10.1186/s12961-019-0441-2
|View full text |Cite
|
Sign up to set email alerts
|

How are evidence generation partnerships between researchers and policy-makers enacted in practice? A qualitative interview study

Abstract: Background Evidence generation partnerships between researchers and policy-makers are a potential method for producing more relevant research with greater potential to impact on policy and practice. Little is known about how such partnerships are enacted in practice, however, or how to increase their effectiveness. We aimed to determine why researchers and policy-makers choose to work together, how they work together, which partnership models are most common, and what the key (1) relationship-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 59 publications
0
40
0
Order By: Relevance
“…A fourth model brings together elements of each of the previous models through largescale knowledge translation platforms [14]. A fifth model concerns knowledge co-production, in which anticipated users of knowledge participate in the knowledgegeneration process [19]. Despite research on these linkages between researchers and policy-makers, much remains unknown about how these relationships are structured [20] and the extent to which experience is transferable across contexts [21].…”
Section: Types Of Knowledgementioning
confidence: 99%
“…A fourth model brings together elements of each of the previous models through largescale knowledge translation platforms [14]. A fifth model concerns knowledge co-production, in which anticipated users of knowledge participate in the knowledgegeneration process [19]. Despite research on these linkages between researchers and policy-makers, much remains unknown about how these relationships are structured [20] and the extent to which experience is transferable across contexts [21].…”
Section: Types Of Knowledgementioning
confidence: 99%
“…decision-makers, managers, implementers) is also knowledge ‘producer’. Founded on principles of collaborative research–practice partnerships ( Kogan and Henkel, 1983 cited in Denis and Lomas, 2003 ; Hanney et al ., 2003 ; Ross et al ., 2003 ) and coproduction theory ( Heaton et al ., 2015 ; Vindrola-Padros et al , 2017 ; Beckett et al ., 2018 ), engaging the ‘knowledge user’ in research has been shown to positively influence the impact of the evidence produced ( Kok et al ., 2016 ; Williamson et al ., 2019 ). In this paper, we conceptualize embedded IR as health system decision-makers taking a prominent role throughout various stages of the research process—starting from the identification of the need for research and the specific implementation problem, to the framing of research questions, data collection and interpretation of findings ( Ghaffar et al ., 2017 ; Tran et al ., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…[4] At the same time, we acknowledge that mobilising knowledge for both policy and practice is a complex and context-dependent process [5], leading to difficulties with achieving partnership in evidence generation. [6] In 2015, we embarked on a project to develop a framework for effective distributed health professions training (DHPT) in South Africa (SA). Distributed training we described as 'training activities for undergraduate [HPE] students that take place away from tertiary academic complexes-for example: health care centres, primary care clinics and district and rural hospitals'.…”
Section: Introductionmentioning
confidence: 99%